IMPLEMENTATION OF PUBLIC RELATIONS MANAGEMENT IN IMPROVING DIGITAL-BASED SERVICE QUALITY AT MI MUHAMMADIYAH GEMPOLSEWU-ROWOSARI-KENDAL - Wagiyanto, Rosyid; Hidayati, Dian (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2023)
This research aims to describe the implementation of public relations management in improving the quality of school services through public relations programs to improve educational services to all school members. This research uses a descriptive qualitative research method. Data collection techniques used were observations, interviews and document studies involving participants. It is through various kinds of data sources that are then analyzed so that, in the end, a conclusion can be drawn. This research shows the importance of public relations management in improving the quality of services in schools. The role of public relations in improving the quality of digital-based education services has seen many changes in education; this is a significant factor in improving the quality of digital-based education services and innovations that are currently developing. Education services, especially in the digital era of education, must design various applications to improve the quality of education services, such as digital registration of new students, digital school graduation announcements, and student assignments accepted, done and collected digitally.